The Synthesis and Pharmacological Properties of Biologically Active Organic Compounds - Alauatdinova Ainagul Inyatdinovna; Nietova Aliya Polatovna; Erimbatova Dilnoza Nurulla qizi (Emerging Frontiers Library for The American Journal of Applied Sciences, 2026)
Biologically active organic compounds play a decisive role in modern medicine and pharmaceutical chemistry. In particular, these compounds are capable of interacting selectively with biological macromolecules, thereby producing therapeutic effects. The present article aims to provide a deeply analyzed overview of synthetic strategies used for obtaining biologically active organic compounds and, furthermore, to examine their pharmacological characteristics. Special emphasis is placed on structure–activity relationships, optimization strategies, and modern trends in medicinal chemistry. Thus, the synthesis and evaluation of such compounds are considered within an integrated scientific framework.